2016
DOI: 10.3329/ajmbr.v2i3.30121
|View full text |Cite
|
Sign up to set email alerts
|

Productive and reproductive performances of Brown Bengal goat (Hilly goat) at research farm level

Abstract: Abstract:A nucleus-breeding flock of selected Brown Bengal goat was established in the Bangladesh Livestock Research Institute (BLRI), Regional Station, Naikhongchari, Bandarban, with the objective of characterization, conservation and improvement of the breed. A total of 69 does of different generations (Foundation = 07, Generation one = 32, Generation two = 23 and Generation three = 07.) and 07 bucks (All were first generation) were used to study the genetic parameters of Brown Bengal goat on productive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Results showed that parity had no significant (P>.05) effect on kid birth weight but significantly (p<0.01) differ of Kid litter weight and litter size (Table 3). Islam et al (2016) and Talukder et al (2010) agrees with the findings that the effects of parity were non-significant (P>0.05) on kid birth weight. Jalil et al (2003) observed that birth weight of kids were no consistent trends according to parity in Black Bengal goat.…”
Section: Effect Of Parity On Kbw Klw and Ls Of Hbb Goatssupporting
confidence: 64%
“…Results showed that parity had no significant (P>.05) effect on kid birth weight but significantly (p<0.01) differ of Kid litter weight and litter size (Table 3). Islam et al (2016) and Talukder et al (2010) agrees with the findings that the effects of parity were non-significant (P>0.05) on kid birth weight. Jalil et al (2003) observed that birth weight of kids were no consistent trends according to parity in Black Bengal goat.…”
Section: Effect Of Parity On Kbw Klw and Ls Of Hbb Goatssupporting
confidence: 64%